Community Empowerment Through Modern Packaging Innovation for Local Superior Products in Tetebatu Village, East Lombok Regency - Sari Novida; Sahwan; Sri Sustini (Unram Journal of Community Service, 2026)
One of the problems often faced by home industry players (IRT) in Tetebatu is product packaging. Product packaging and design is an effective way as a promotional medium. Household products in Tetebatu village are still less varied so they look less attractive. The better the product packaging, the higher the expectation of increased sales which have an impact on the economic welfare of the community. The purpose of this pkm is to provide insight and skills to target partners about packaging and all things that bind the kemesan, be it design, information on products and legality. The method used in this pkm is socialization and training. The target partners are home industry players who have not realized the importance of packaging to increase sales, sales strategies and promotion. The pkm team together with the unizar technology business incubator provided several socializations and training for target partners including socialization of product packaging, socialization of the introduction of product packaging tools and machines and training on the types and packaging of products that can be used by partners. The visible results after the community service was carried out resulted in several modern and innovative packages, so that it will have an impact on Tetebatu tourism becoming more modern and innovative.